2016
DOI: 10.1158/1538-7445.am2016-750
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 750: Nanoliposomal targeting of Ephrin receptor A2 (EphA2): Clinical translation

Abstract: Ephrin receptor A2 (EphA2) is part of the Ephrin family of cell-cell junction proteins highly overexpressed in several solid tumors, and is associated with poor prognosis. We developed a novel EphA2-targeted docetaxel nanoliposome, leveraging organ specificity through enhanced permeability effect and cellular specificity through EphA2 targeting. The goal of the study was to develop the diagnostic framework enabling the clinical implementation of EphA2-based exclusion criteria in future MM-310 trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Merrimack Pharmaceuticals (Cambridge, MA), who developed Onivyde earlier, is currently investigating (NCT03076372) an ephrin receptor A2 (EphA2) antibodydirected liposomal docetaxel in solid tumors, including gastric and pancreatic cancer. The immunohistochemistry of clinical tumor samples was used to develop a framework for screening patients for inclusion in the clinical trial based on EphA2 expression in the patient's tumor (Kamoun et al, 2016). Overall, these approaches suggest that liposomes have many advantages in mitigating the cytotoxicity of chemotherapeutics and other small molecules, and in augmenting therapeutic benefit by improving drug delivery and release in the tumor.…”
Section: Payloads and Applications In Gi Cancer Therapymentioning
confidence: 99%
“…Merrimack Pharmaceuticals (Cambridge, MA), who developed Onivyde earlier, is currently investigating (NCT03076372) an ephrin receptor A2 (EphA2) antibodydirected liposomal docetaxel in solid tumors, including gastric and pancreatic cancer. The immunohistochemistry of clinical tumor samples was used to develop a framework for screening patients for inclusion in the clinical trial based on EphA2 expression in the patient's tumor (Kamoun et al, 2016). Overall, these approaches suggest that liposomes have many advantages in mitigating the cytotoxicity of chemotherapeutics and other small molecules, and in augmenting therapeutic benefit by improving drug delivery and release in the tumor.…”
Section: Payloads and Applications In Gi Cancer Therapymentioning
confidence: 99%
“…Recent work by our group , and others demonstrated that combination therapies using light-activated nanoconstructs synergistically enhance efficacy. These, along with ongoing clinical efforts to introduce molecular specificity to chemotherapy-encapsulating nanomedicines for PDAC and other cancers (MM-310, Ephrin A2 targeted liposomal docetaxel), accentuate the high translational potential of our Cet-PINs. As a proof of concept, we also show that encapsulation of the front-line PDAC chemotherapeutics gemcitabine hydrochloride, 5-fluorouracil, and oxaliplatin, within the Cet-PINs, yields chemo-per-Cet payloads that are not achievable with direct antibody conjugates.…”
mentioning
confidence: 99%